Uji Efektifitas Ekstrak Etanol Bawang Tiwai (Eleutherine americana Merr) Terhadap Keadaan Klinis Tikus Periodontitis Yang Diinduksi Porphyromonas gingivalis - Ibrahim, Jamilah; Yani, Sinar; Irawiraman, Hadi (Mulawarman Dental Journal, 2021)
Background: Periodontitis is inflammation and infection that occurs in the periodontal tissue and alveolar bone supporting the teeth. Periodontal tissue examination should be performed to determine the severity of a periodontal disease. There are various kinds of examinations such as gingival index measurement, probing depth measurement, & bleeding on probing examination. Tiwai onions (Eleutherine americana Merr) have anti-inflammatory effects through the content of flavonoids and phenolic compounds. Objective: This study aims to determine the anti-inflammatory effectiveness of the ethanol extract of tiwai onion (Eleutherine americana Merr) against the clinical condition of post Porphyromonas gingivalis induced periodontitis rats.Method: The study was a true experimental method with the Posttest Only and Control Group Design method. The bacteria used was Porphyromonas gingivalis ATCC® 33277. This study consisted of 5 treatment groups using ethanol extracts of tiwai onions leaves with a concentration 140 mg/kg BW, 280 mg/kg BW, 560 mg/kg BW, sodium diclofenac 9 mg/kg BW and CMC. Data obtained by measuring the diameter of the gingival edema. Statistical analysis by using One Way Anova.Results: The ethanol extract of tiwai onion has an effect at a dose of 560 mg / kgBW on the clinical condition of the periodontal tissue by measuring the gingival index, periodontal depth and bleeding on probing in periodontitis rats.Conclusion: The ethanol extract of tiwai dose has an effect on the clinical condition of periodontal tissue by measuring the gingival index, periodontal depth and bleeding on probing in preventing periodontitis in male white wistar rats after Porphyromonas gingivalis induction at a dose of 560 mg / kg BW. Keywords: Eleutherine Americana Merr, Porphyromonas gingivalis, Periodontitis, gingival index, periodontal depth, bleeding on probing